Development of quantitative mass spectrometric immunoassay for serum amyloid A. (16th November 2016) - Trenchevska, Olgica; Yassine, Hussein N.; Borges, Chad R.; Nelson, Randall W.; Nedelkov, Dobrin
Abstract: Objective: Proteins can exist as multiple proteoforms in vivo that can have important roles in physiological and pathological states. Methods: We present the development and characterization of mass spectrometric immunoassay (MSIA) for quantitative determination of serum amyloid A (SAA) proteoforms. Results: Intra- and inter-day precision revealed CVs <10%. Against existing SAA ELISA, the developed MSIA showed good correlation according to the Altman–Bland plot. Individual concentrations of the SAA proteoforms across a cohort of 170 samples revealed 7 diverse SAA polymorphic types and 12 different proteoforms. Conclusion: The new SAA MSIA enables parallel analysis of SAA polymorphisms and quantification of all expressed SAA proteoforms, in a high-throughput and time-efficient manner.